Mixed lineage kinase domain-like protein induces RGC-5 necroptosis following elevated hydrostatic pressure. (22nd August 2017) - Liao, Lvshuang; Shang, Lei; Li, Na; Wang, Shuchao; Wang, Mi; Huang, Yanxia; Chen, Dan; Huang, Jufang; Xiong, Kun
Abstract: Receptor-interacting protein 3 (RIP3) is an essential component of the necroptosis signaling pathway. Phosphorylation of its downstream target, mixed lineage kinase domain-like protein (MLKL), has been proposed to induce necroptosis by initiating Ca 2+ influx. Our previous studies have shown that RGC-5 retinal ganglion cells undergo RIP3-mediated necroptosis following elevated hydrostatic pressure (EHP). However, the molecular mechanism underlying necroptosis induction downstream of RIP3 is still not well understood. Here, we investigated the effects of MLKL during EHP-induced necroptosis, and primarily explored the relationship between MLKL and Ca 2+ influx. Immunofluorescence staining showed that the expression of MLKL was increased 12 h after EHP. Western blot analysis demonstrated that the phosphorylated and unphosphorylated forms of both RIP3 and MLKL were up-regulated 12 h after EHP, while inhibition of RIP3 by GSK′872 decreased the expression of phosphorylated MLKL at the same stage. Propidium iodide staining, lactate dehydrogenase release assays, flow cytometry, and electron microscopy revealed the increased necrosis of RGC-5 cells 12 h after EHP, which coincided with elevated cytosolic Ca 2+ concentrations. Depletion of extracellular Ca 2+ and siRNA-mediated silencing of MLKL significantly reduced EHP-induced necrosis. Both MLKL-specific siRNA and GSK′872 treatment diminished Ca 2+ influx. Thus, our findings suggest that MLKL may be the key mediator of necroptosis downstream of RIP3 phosphorylation and may be involved in increasing intracellular Ca 2+ concentrations in EHP-induced RGC-5 necroptosis.